Small and Medium Enterprises Business Strategy in Pandemic COVID-19 - Darwis Harahap; Ferry Alfadri; Ayu Damayanti (Universitas Islam Negeri Alauddin Makassar, 2020)
The COVID-19 pandemic that has hit the world including Indonesia since early 2020 has had a significant impact on the Indonesian economy, especially in the Small and Medium Enterprises (SME’s) sector. This study aims to determine an efficient business strategy to survive the COVID-19 pandemic in Padangsidimpuan City. This study uses descriptive qualitative analysis techniques with semi-structured interview methods using purposive sampling in selecting sources and then analyzed with SWOT analysis and described in the form of a matrix so as to produce several alternative SME’s business strategies during the COVID-19 pandemic. The results showed that several sectors in Padangsidimpuan City felt the direct impact of the COVID-19 pandemic, such as the areas of public transportation and tourism which experienced a decline. Meanwhile, in the food sector it is still stable, but in services such as expeditions and delivery it has increased. The narrow space of movement between sellers and buyers that is happening now makes selling online the main solution. Businesses need to open up insight in thinking to start choosing e-marketing as a promotional path for goods and services to increase the number of sales transactions while still adhering to health protocols.